2015
DOI: 10.1038/laban.732
|View full text |Cite
|
Sign up to set email alerts
|

An ultrasound-guided technique for axillary brachial plexus nerve block in rabbits

Abstract: Regional anesthesia techniques, such as nerve blocks, are routinely used in humans and can contribute to multimodal approaches to pain management in research animals. Ultrasound guidance is an emerging aspect of regional anesthesia that has the potential to optimize local delivery and distribution of anesthetic agents, thereby reducing the amounts of these agents that must be administered. The authors developed an ultrasound-guided technique for effective block of the axillary brachial plexus in rabbits. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
2
14
1
Order By: Relevance
“…Therefore, one can administer the appropriate minimum quantity to soak these nerve structures. In the above study 8 , the researchers mentioned a reduction of 12.5 to 25% of the volume of anesthetic in some animals without reducing the duration of sensory and motor blockade. Furthermore, reducing the volume of the local anesthetic makes the procedure safer regarding poisoning, which is common in animals with small body weight.…”
Section: Identification Of Individual Structures Was Possible Mainly Bymentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, one can administer the appropriate minimum quantity to soak these nerve structures. In the above study 8 , the researchers mentioned a reduction of 12.5 to 25% of the volume of anesthetic in some animals without reducing the duration of sensory and motor blockade. Furthermore, reducing the volume of the local anesthetic makes the procedure safer regarding poisoning, which is common in animals with small body weight.…”
Section: Identification Of Individual Structures Was Possible Mainly Bymentioning
confidence: 97%
“…This goal can be more effectively achieved by using sonographic visualization rather than being performed blindly. Furthermore, a recent study performed with rabbits showed that this combination of techniques enables successful nerve block in a short time 8 . In our study, we reproduce the technique with ease successfully in all the animals tested.…”
Section: Identification Of Individual Structures Was Possible Mainly Bymentioning
confidence: 98%
See 1 more Smart Citation
“…The results suggest the clinical feasibility of ultrasoundguided brachial plexus block in bovine medicine [21].According to Gofeld et al (2013), ultrasonography is an alternative imaging method for localization and examination of peripheral nerves and allows serial examinations over almost any anatomical region so that a long length of a nerve can be studied under dynamic conditions where changes in body position or orientation may influence the nerve's location [16]. Fonseca et al (2015) stated that ultrasound guidance is an emerging aspect of regional anesthesia that has the potential to optimize local delivery and distribution of anesthetic agents in rabbits, thereby reducing the amounts of these agents that must be administered. They recommend that this technique be integrated into multimodal approaches to pain management in rabbits undergoing thoracic limb surgery [10].…”
Section: Introductionmentioning
confidence: 96%
“…Fonseca et al (2015) stated that ultrasound guidance is an emerging aspect of regional anesthesia that has the potential to optimize local delivery and distribution of anesthetic agents in rabbits, thereby reducing the amounts of these agents that must be administered. They recommend that this technique be integrated into multimodal approaches to pain management in rabbits undergoing thoracic limb surgery [10]. Ghadirian et al, 2016 did the comparison of lidocaine, lidocaine-morphine, lidocainetramadol or bupivacaine for neural blockade of the brachial plexus in fat-tailed lambs and concluded that the addition of morphine or tramadol to lidocaine did not affect the duration of antinociception of lidocaine for brachial plexus block in fat-tailed lambs [14].…”
Section: Introductionmentioning
confidence: 99%